2012
DOI: 10.1007/s00265-012-1322-7
|View full text |Cite
|
Sign up to set email alerts
|

Body size, demography and foraging in a socially plastic sweat bee: a common garden experiment

Abstract: Phenotypic plasticity may evolve when conditions vary temporally or spatially on a small enough scale. Plasticity is thought to play a central role in the early stages of evolutionary transitions, including major transitions such as those between non-sociality and sociality. The sweat bee Halictus rubicundus is of special interest in this respect, because it is socially plastic in the British Isles: Nests are social or non-social depending on the environment. However, sociality comprises a complex suite of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 41 publications
2
72
0
Order By: Relevance
“…Yanega 1997; Field et al 2010, 2012; Kapheim et al 2012, 2015a; Kocher et al 2013; Rehan and Toth 2015), and investigating these mechanisms requires taxa that straddle this transition (Field et al 2010; Rehan and Toth 2015). Socially polymorphic sweat bees (Hymenoptera: Halictidae) are ideal models for this purpose, because different populations of the same species exhibit either eusocial or solitary behaviour (Soucy and Danforth 2002; Chapuisat 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yanega 1997; Field et al 2010, 2012; Kapheim et al 2012, 2015a; Kocher et al 2013; Rehan and Toth 2015), and investigating these mechanisms requires taxa that straddle this transition (Field et al 2010; Rehan and Toth 2015). Socially polymorphic sweat bees (Hymenoptera: Halictidae) are ideal models for this purpose, because different populations of the same species exhibit either eusocial or solitary behaviour (Soucy and Danforth 2002; Chapuisat 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Field transplants are critical to addressing this question and yet are rarely performed (Yanega 1997; Field et al 2012). Reciprocal transplants of the socially polymorphic sweat bee Halictus rubicundus Christ between social and solitary populations in the UK revealed that social phenotype is plastic with respect to the environment (Field et al 2010, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations